Pengaruh Kepercayaan, Pengetahuan Dan Sikap Terhadap Akses Jamban Di Perkotaan - Mila Mardotillah; Budhi Gunawan; Rini Soemarwoto; Ardini Raksanagara (Institut Teknologi Sepuluh Nopember, 2019)
The difficulty access of urban-city healthy latrines are influenced by population density, limitation of infrastructure and high mobility. Cultural factors become one of the key in influencing people’s behavior to access healthy latrines. The aim this research is to explore the culture factors influencing to access healthy latrine. The method uses a retrospective quantitative approach with cross sectional analytical method (cross sectional) to know the cultural factors that exist in shaping people's behaviour in using healthy latrines.The findings of this research are the cultural factors related to access of healthy latrines which studied include belief on the taboo, gender, beliefs and differences of each generation. The significant influential factors are trust, knowledge and attitude. While other factors simultaneously affect the citizen in behaving using healthy latrines.The conclusion is that the behaviour created by individual knowledge, attitudes and actions in accessing healthy latrines, it will be established and successful if the cultural factor approach is carried out simultaneously. The concept of a person about something is the impact of the way of thinking about something based on the culture containing non-individual but public meaning, so when the system of meaning belongs to the collective society, society can have the same pattern of behaviour. The cultural factors can serve as a basis for improving urban residents' access to healthy latrines.